Isolation of CYP3A4 Inhibitors from the Black Cohosh (Cimicifuga racemosa). Issue 2 (2005) - Tsukamoto, Sachiko; Aburatani, Maki; Ohta, Tomihisa
Abstract : Recent investigation on drug interaction has shown that some foods and herbal medicines increase the oral availability of a variety of CYP3A4 substrates, which is caused by the reduction of CYP3A4 in intestinal epithelium. During the course of our investigation on CYP3A4 interaction, we found that the commercially available dietary supplement made from black cohosh ( Cimicifuga racemosa ) showed CYP3A4 inhibition. Black cohosh has been used for the treatment of menopausal and post-menopausal symptoms as a dietary supplement. Bioassay-guided isolation from the supplement afforded six active principles, which were identified as cycloartanoid triterpene glycosides.